From ice core to ground-penetrating radar: representativeness of SMB at three ice rises along the Princess Ragnhild Coast, East Antarctica - Cavitte, Marie G.P.; Goosse, Hugues; Wauthy, Sarah; Kausch, Thore; Tison, Jean-Louis; Van Liefferinge, Brice; Pattyn, Frank; Lenaerts, Jan T.M.; Claeys, Philippe (Journal of Glaciology, 2022)
The future contributions of the Antarctic Ice Sheet to sea level rise will depend on the evolution of its surface mass balance (SMB), which could amplify/dampen mass losses increasingly observed at the ice sheet's edge. In situ constraints of SMB over annual-to-decadal timescales consist mostly of firn/ice cores that have a surface footprint cm. SMB constraints also come from climate models, which have a higher temporal resolution but a larger surface footprint of several km. We use ice-penetrating radar data to obtain an intermediate spatial and temporal resolution SMB record over three ice rises along the Princess Ragnhild Coast. The co-located ice cores allow us to obtain absolute radar-derived SMB rates at a multi-annual-to-decadal temporal resolution. By comparing the ice core SMB measurements and the radar-derived SMB records, we determine that pointwise measurements of SMB are representative of a small surface area, m radius extending from the ice core drill site for the ice rises studied here, and that the pointwise measurements are systematically 7–15 cm w.e. a lower than the mean SMB value calculated for the whole ice rises. However, ice core records are representative of an entire ice rise's temporal variability at the temporal resolution examined.